Rediscovering the Chemistry of Sulfur Dioxide: New Developments in Synthesis and Catalysis - Deeming, Alex S.; Emmett, Edward J.; Richards-Taylor, Charlotte S.; Willis, Michael C. (Synthesis, 2014)
The recent development of several sulfur dioxide surrogates has seen a renaissance in its chemistry, with a number of new synthetic methods being reported. This article reviews the reactions of sulfur dioxide and sulfur dioxide surrogates, with an emphasis on recent examples.1 Introduction2 Sulfur Dioxide Surrogates3 Reactions with Organometallic Reagents4 Pericyclic Reactions5 Sulfur Dioxide Radical Chemistry6 Transition-Metal-Catalysed Processes7 Conclusions
Keywords: sulfur dioxide; surrogate; sulfinate; metal catalysis; sulfone; sulfonamide